Simulating rewetting events in intermittent rivers and ephemeral streams: A global analysis of leached nutrients and organic matter. (25th February 2019) - Shumilova, Oleksandra; Zak, Dominik; Datry, Thibault; von Schiller, Daniel; Corti, Roland; Foulquier, Arnaud; Obrador, Biel; Tockner, Klement; Allan, Daniel C.; Altermatt, Florian; Arce, María Isabel; Arnon, Shai; et al.
Abstract: Climate change and human pressures are changing the global distribution and the extent of intermittent rivers and ephemeral streams (IRES), which comprise half of the global river network area. IRES are characterized by periods of flow cessation, during which channel substrates accumulate and undergo physico‐chemical changes (preconditioning), and periods of flow resumption, when these substrates are rewetted and release pulses of dissolved nutrients and organic matter (OM). However, there are no estimates of the amounts and quality of leached substances, nor is there information on the underlying environmental constraints operating at the global scale. We experimentally simulated, under standard laboratory conditions, rewetting of leaves, riverbed sediments, and epilithic biofilms collected during the dry phase across 205 IRES from five major climate zones. We determined the amounts and qualitative characteristics of the leached nutrients and OM, and estimated their areal fluxes from riverbeds. In addition, we evaluated the variance in leachate characteristics in relation to selected environmental variables and substrate characteristics. We found that sediments, due to their large quantities within riverbeds, contribute most to the overall flux of dissolved substances during rewetting events (56%–98%), and that flux rates distinctly differ among climate zones. Dissolved organic carbon, phenolics, and nitrate contributed most to the areal fluxes. The largest amounts of leached substances were found in the continental climate zone, coinciding with the lowest potential bioavailability of the leached OM. The opposite pattern was found in the arid zone. Environmental variables expected to be modified under climate change (i.e. potential evapotranspiration, aridity, dry period duration, land use) were correlated with the amount of leached substances, with the strongest relationship found for sediments. These results show that the role of IRES should be accounted for in global biogeochemical cycles, especially because prevalence of IRES will increase due to increasing severity of drying events. Abstract : In this study we experimentally simulated under laboratory conditions rewetting of leaves, riverbed sediments, and epilithic biofilms collected during the dry phase from intermittent rivers and ephemeral streams covering global spatial scale. We determined the amounts and quality of the leached nutrients and dissolved organic matter, assessed their inter‐substrate and cross‐climate differences, and estimated areal fluxes from 1 m 2 of riverbeds. In addition, we evaluated the variance in leachate characteristics related to selected environmental variables and substrate characteristics.